Using the CIPP Model to elicit perceptions of health professions faculty and students about virtual learning - Sakineh Gerayllo; Mohammadali Vakili; Leila Jouybari; Zahra Moghadam; Ali Jafari; Alireza Heidari (BMC Medical Education)
Abstract Background The outbreak of the Coronavirus epidemic has caused a huge crisis initiating fundamental changes in education since this crisis has turned face-to-face education into virtual training. This questionnaire-based study employed the comprehensive CIPP Model (Context, Input, Process, Product) to obtain the perspectives of both faculty members and students from six different faculties at one university in Iran concerning implementation of virtual learning in during COVID 19. Methodology The participants in this cross-sectional study were 522 students and 38 members of the faculty in six different faculties who were selected via stratified random sampling. The research tool was a validated and reliable researcher-made questionnaire developed based on the context, input, process, and product (CIPP) evaluation model. The survey included a scale for each of the four CIPP components, with scales comprised of 9 to 12 questions. The data were analyzed through SPSS 23 using descriptive and inferential (Mann–Whitney, Kruskal–Wallis, and Spearman correlation) methods. Results The scale items for each of the CIPP components that elicited the highest levels of agreement by both professors and students were as follows based on a five point scale where higher scores indicated higher levels of respondent agreement: Context: Topics presented in the virtual training are determined according to the course plan (3.63), and virtual education reduces the teacher's control over class (3.56); Input: Designated hours are suitable for virtual learning classes (3.29); Process: Professors have less commitment and responsibility in providing virtual courses (3.48); and Product: Student participation in virtual classes is low (3.78), and virtual learning saves time (3.67).” For both students and faculty, the mean scores for the context, input, process, and product scales all averaged near the mid-point of the scale, 3.00. No significant difference was observed between professors and students except for the input construct. Students responded significantly differently according to their age and educational level on the product construct, and significantly differently according to their faculty and marital status on each of the CIPP constructs. Conclusion This study has highlighted various issues related to virtual education, and the opinions of professors and students regarding changes to the online educational program should be strategically considered. The present findings can facilitate decision-making and policy-making at the macro level, enabling officials to plan appropriately, take professional measures, and decide whether to continue, cease, or revise educational goals, inputs, processes, and products.